2015
DOI: 10.1021/nn506928p
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Decorated Doxorubicin-Encapsulated Nanoparticle Targets and Eliminates Tumor Reinitiating Cancer Stem-like Cells

Abstract: Tumor reinitiating cancer stem-like cells are responsible for cancer recurrence associated with conventional chemotherapy. We developed a doxorubicin-encapsulated polymeric nanoparticle surface-decorated with chitosan that can specifically target the CD44 receptors of these cells. This nanoparticle system was engineered to release the doxorubicin in acidic environments, which occurs when the nanoparticles are localized in the acidic tumor microenvironment and when they are internalized and localized in the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 255 publications
(189 citation statements)
references
References 58 publications
8
179
0
2
Order By: Relevance
“…74 A number of nanodelivery systems have been developed to target CD44 receptor using different targeting moieties (Table 6). [75][76][77][78] Besides anti-CD44 monoclonal antibodies, hyaluronic acid is also a popular ligand for CD44 targeting, as CD44 is a receptor of hyaluronic acid. 74 Other valuable targets of BCSC include CD133.…”
Section: Nanotherapy Of Breast Cancer Stem Cells (Bcscs)mentioning
confidence: 99%
“…74 A number of nanodelivery systems have been developed to target CD44 receptor using different targeting moieties (Table 6). [75][76][77][78] Besides anti-CD44 monoclonal antibodies, hyaluronic acid is also a popular ligand for CD44 targeting, as CD44 is a receptor of hyaluronic acid. 74 Other valuable targets of BCSC include CD133.…”
Section: Nanotherapy Of Breast Cancer Stem Cells (Bcscs)mentioning
confidence: 99%
“…2c). While the reasons for these localization behaviors are still largely unclear, it has previously been reported that chitosan can bind to CD44 receptors of cancer stem cells 161 and a similar receptor-mediated mechanism may be responsible where the neurites may present membrane receptors that can bind to starch. …”
Section: Location and Uptake Of Mnpsmentioning
confidence: 99%
“…For instance, Amiji's group developed a series of CD44-targeting HA-based self-assembling nanosystems for siRNA delivery and observed enhanced delivery efficiency and gene silencing activity of siRNA loaded in selected HA nanosystems in drug-resistant CD44 receptor-overexpressing tumour models [160]. Recently, they devised a nanodrug (nanodoxorubicin or nDOX) system by encapsulating DOX in nanoparticles synthesised using Pluronic F127 cross-linked and surface-decorated with chitosan, the chemical structure of which resembles that of HA [161]. The authors proved that nDOX significantly increased the cytotoxicity of doxorubicin in comparison to free doxorubicin for eliminating CD44 þ CSCs residing in 3D mammary tumour spheroids, and showed that nDOX could reduce the size of tumours in an orthotopic xenograft tumour model with no evident systemic toxicity (Fig.…”
Section: Application Of Targeted Nanocarriers For Csc Therapymentioning
confidence: 99%